2006
DOI: 10.1097/01.qai.0000225319.59652.1e
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Evaluating Time to CD4 T-cell Count <350 cells/mm3 After Treatment Interruption Following Antiretroviral Therapy ± Interleukin 2: Results of ACTG A5102

Abstract: IL-2 before TI did not prolong time to CD4 of less than 350 cells/mm. A TI strategy utilizing a CD4 T-cell threshold of less than 350 cells/mm for restarting ART appears generally safe with most subjects in both arms remaining off ART for more than 1 year. Implications of our results for TI strategies include the potential advantage of starting ART at higher CD4 T-cell levels while avoiding any drug resistance and evaluating immunomodulators or drugs to reduce T-cell activation and HIV-1 RNA rebound during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…Many studies have shown that the slope of the decrease in CD4 cell count after TI is biphasic, there being an initial fast drop, followed by a slower decrease [9][10][11]16,18,19,28,29]. This observation was confirmed by our findings.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Many studies have shown that the slope of the decrease in CD4 cell count after TI is biphasic, there being an initial fast drop, followed by a slower decrease [9][10][11]16,18,19,28,29]. This observation was confirmed by our findings.…”
Section: Discussionsupporting
confidence: 82%
“…Attempts have been made in numerous studies to evaluate possible differences in the evolution of HIV infection in men compared with women. However, according to a recent review [27], none of the studies demonstrated a statistically significant effect of sex on disease progression, but most found somewhat slower rates of progression to AIDS and death in women than in men.Many studies have shown that the slope of the decrease in CD4 cell count after TI is biphasic, there being an initial fast drop, followed by a slower decrease [9][10][11]16,18,19,28,29]. This observation was confirmed by our findings.…”
supporting
confidence: 82%
See 3 more Smart Citations